Application of participation in clinical practice: Key issues - Dominique van de Velde; Marieke Coussens; Stijn De Baets; Lode Sabbe; Guy Vanderstraeten; Peter Vlerick; Lien Van Malderen; Ellen Gorus; Patricia De Vriendt (Medical Journals Sweden, 2018)
Background: Rehabilitation services are increasingly targeting involvement in daily life. In the International Classification of Functioning, Disability and Health this is referred to as "participation". How-ever, questions have arisen regarding the conceptualization of participation, and consensus is lacking. Methods: The first phase of this study is a critical review of the literature to detect recurring conceptual problems in the application of participation and how researchers deal with these. The second phase is a systematic review to identify how participation measures are operationalized. Results: The critical review found possible solutions to 4 recurring key limitations: (i) how to deal with ambiguity and vagueness regarding the term "participation"; (ii) how to differentiate between activity and participation; (iii) what is the current empirical knowledge about the subjective aspects of participation; (iv) what are the different ways to measure participation. The systematic review found 18 instruments operationalizing participation in different ways: (i) unidimensional: frequency of performing activities; (ii) unidimensional: limitations in experiencing participation when performing activities; (iii) multidimensional: multiple subjective dimensions when performing activities; and (iv) multidimensional: objective and subjective dimensions. Discussion and conclusion: Notwithstanding an increasing body of knowledge, some issues remain unclear and how participation is measured is subject to debate. This results in difficulties in the use of participation in clinical practice. However, insight into the current body of knowledge and awareness of shortcomings might help clinicians who aim to apply participation in practice.